Industry Wage Differentials: A Firm-Based Approach - Card, David; Rothstein, Jesse; Yi, Moises (Journal of Labor Economics, 2024)
We revisit the estimation of industry wage differentials using linked employer-employee data. Cross-sectional industry differences overstate pay premiums due to unmeasured heterogeneity. Estimates based on models with person and industry effects understate true premiums: workers who switch to a higher-premium industry typically move from higher-paying firms in their origin industry to lower-paying firms in their destination (and vice versa). The corrected standard deviation of log wage effects is 0.122 across narrowly defined industries and is similar at higher levels of aggregation. Higher-skilled workers sort to higher-pay industries. Premiums and worker sorting are more variable in cities with higher-wage firms and higher-skilled workers.